Gradient of Expression of Dopamine D2 Receptors Along the Dorso-Ventral Axis of the Hippocampus - Dubovyk, Valentyna; Manahan-Vaughan, Denise (Frontiers in Synaptic Neuroscience, 2019)
Dopamine D2-like receptors (D2R) play an important role in the regulation of hippocampal neuronal excitability and contribute to the regulation of synaptic plasticity, the encoding of hippocampus-dependent memories and the regulation of affective state. In line with this, D2R is targeted in treatment of psychosis and affective disorders. It has been proposed that the dorso-ventral axis of the hippocampus can be functionally delineated into the dorsal pole that predominantly processes spatial information and the ventral pole that mainly addresses hippocampal processing of emotional and affective state. Although dopaminergic control of hippocampal information processing has been the focus of a multitude of studies, very little is known about the precise distribution of D2R both within anatomically defined sublayers of the hippocampus and along its dorsoventral axis, that could in turn yield insights as to the functional significance of this receptor in supporting hippocampal processing of spatial and affective information. Here, we used an immunohistochemical approach to precisely scrutinize the expression of D2R both within the cellular and dendritic layers of the hippocampal subfields, and along the dorso-ventral hippocampal axis. In general, we detected significantly higher levels of expression of D2R in the ventral, compared to the dorsal poles with regard to the CA1, CA2, CA3 and dentate gyrus regions. Effects were very consistent: the molecular layer, granule cell layer and polymorphic layer of the dentate gyrus exhibited higher D2R levels in the ventral compared to dorsal hippocampus. D2R levels were also significantly higher in the ventral Stratum oriens, Stratum radiatum, and Stratum lacunosum-moleculare layers of the CA1 and CA3 regions. The apical dendrites of the ventral CA2 region also exhibited higher D2R expression compared to the dorsal pole. Taken together, our study suggests that the higher D2R expression levels of the ventral hippocampus may contribute to reported gradients in the degree of expression of synaptic plasticity along the dorso-ventral hippocampal axis, and may support behavioral information processing by the ventral hippocampus.